If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -1y + 4z = 32 Solving 3x + -1y + 4z = 32 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'y' to each side of the equation. 3x + -1y + y + 4z = 32 + y Combine like terms: -1y + y = 0 3x + 0 + 4z = 32 + y 3x + 4z = 32 + y Add '-4z' to each side of the equation. 3x + 4z + -4z = 32 + y + -4z Combine like terms: 4z + -4z = 0 3x + 0 = 32 + y + -4z 3x = 32 + y + -4z Divide each side by '3'. x = 10.66666667 + 0.3333333333y + -1.333333333z Simplifying x = 10.66666667 + 0.3333333333y + -1.333333333z
| 3x-y+4x=32 | | (-12x+13)=73 | | x-3y+5=x-y+1 | | 12.5+s=21.2 | | 5+2e=3(e)-2 | | (-12x+13)= | | (X)25=-2 | | m-2.25=19.75 | | 45=6X+15 | | 13/12 | | y+0=-4 | | (2/3n)*(3/2) | | (3/2n)*(2/3) | | 10-2x=-18 | | 2/3n*3/2 | | 64w^2+80wx+25x^2=0 | | w-12=-8 | | 12x-7=12x | | -1=log(x+3) | | -25(0)+y=55 | | a-200=100 | | 3x=9+x+1 | | (3sinx)(3cosx)= | | -25x+0=55 | | 4x^2+26x=48 | | 4x^2+26=48 | | -(x-5)=2x-4 | | Ln(5x-4)=3 | | 10x+5x-3=8x+12 | | 9+s=-20 | | 30*x^2= | | 72.2=y-21.2 |